2022
DOI: 10.3389/fonc.2022.1020121
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and harnessing triple-negative breast cancer-related microbiota in oncology

Abstract: Bacterial inhabitants of the body have the potential to play a role in various stages of cancer initiation, progression, and treatment. These bacteria may be distal to the primary tumour, such as gut microbiota, or local to the tissue, before or after tumour growth. Breast cancer is well studied in this context. Amongst breast cancer types, Triple Negative Breast Cancer (TNBC) is more aggressive, has fewer treatment options than receptor-positive breast cancers, has an overall worse prognosis and higher rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 250 publications
0
5
0
Order By: Relevance
“…The microbial profiles found in adjacent normal tissue were more similar to the tumor microbiome than those found in nonmatched healthy tissue controls, suggesting that the TME resident tumor microbiota can extend to surrounding tissues, implying an active role in tumorigenesis. 13,43,51 Recent evidence also supports the idea that intra-tumoral bacteria can localize within the tumor and immune cells in various cancer types, including TNBC. Intriguingly, recent studies suggest that the influence of gut microbiome on tumor-infiltrating lymphocytes (TILs) profile is associated with better treatment outcomes in TNBCs and other cancers.…”
Section: Microbiome and Breast Cancermentioning
confidence: 71%
See 3 more Smart Citations
“…The microbial profiles found in adjacent normal tissue were more similar to the tumor microbiome than those found in nonmatched healthy tissue controls, suggesting that the TME resident tumor microbiota can extend to surrounding tissues, implying an active role in tumorigenesis. 13,43,51 Recent evidence also supports the idea that intra-tumoral bacteria can localize within the tumor and immune cells in various cancer types, including TNBC. Intriguingly, recent studies suggest that the influence of gut microbiome on tumor-infiltrating lymphocytes (TILs) profile is associated with better treatment outcomes in TNBCs and other cancers.…”
Section: Microbiome and Breast Cancermentioning
confidence: 71%
“…Other studies have shown that TNBC has the least taxonomic diversity among all breast cancer types and a higher abundance of biofilm‐forming bacterial strains, such as Aggregatibacter and Caulobacter . The microbial profiles found in adjacent normal tissue were more similar to the tumor microbiome than those found in non‐matched healthy tissue controls, suggesting that the TME resident tumor microbiota can extend to surrounding tissues, implying an active role in tumorigenesis 13,43,51 . Recent evidence also supports the idea that intra‐tumoral bacteria can localize within the tumor and immune cells in various cancer types, including TNBC.…”
Section: Microbiome and Breast Cancermentioning
confidence: 75%
See 2 more Smart Citations
“…In TNBC, however, the negative impact of microbiota-mediated oestrogen abundance does not seem to occur, likely due to the lack of ERa expression. TNBCs have alternative oestrogen signalling pathways which render them responsive to circulating hormones [ 124 ]. Interestingly, studies suggest that receptors such as ERb, G protein-coupled oestrogen receptor 1, and oestrogen-related receptors have anti-cancer effects and that, when these are expressed in TNBCs, prognosis seems to be better [ 125 ].…”
Section: Triple Negative Breast Cancer (Tnbc)mentioning
confidence: 99%